Characterization of Excavated Radionuclide Retention Ponds in a Uranium Mine in the Process of Decommissioning Using Geophysical Methods - Netto, Leonides Guireli [UNESP] (2024)
The challenges inherent in mining environmental liabilities, especially in radioactive mineral contexts, highlight the crucial importance of rehabilitating and properly managing degraded areas and tailings. In radioactive minerals mining, the challenges are accentuated due to the complexity of the materials and the environmental risks associated with persistent radioactivity. This scenario underlines the critical need for precise environmental management strategies, highlighting the importance of geophysical techniques for monitoring and mitigating environmental risks in radionuclide retention ponds. Geophysical techniques, such as electrical tomography and seismic tomography refraction, are interesting tools for identifying anomalies in the subsoil, such as leaks, fractures and contamination zones, which are not visible on the surface. These methods provide a non-invasive means of continuously monitoring the integrity of tailings storage facilities, allowing for early detection of potential failures or contamination pathways. By offering a more spatial understanding of subsurface conditions compared to traditional geotechnical instrumentation, geophysics plays an important role in mitigating environmental impacts, reducing risks to nearby ecosystems and informing rehabilitation efforts in radioactive mineral mining areas. This study applied electrical and seismic methods to assess two retention ponds at a uranium mine, demonstrating how these techniques can help in the safe decommissioning of mining facilities and the sustainable management of environmental liabilities. With a focus on two retention ponds of a uranium mine in South America in the process of decommissioning, the results revealed conductive electrical anomalies and variations in the geological layers identified by electrical tomography and refraction seismic, respectively, indicating potentially contaminated areas and alterations in the degree of fracturing of the foundation rock of the ponds. Comparing these results with a structural survey of fracture orientations in the study area demonstrates the preferential path of underground flow, conditioned by the fracturing pattern of the weathered rocks. These findings emphasize the importance of geophysics in the decommissioning phase of nuclear facilities, not only to monitor stored environmental liabilities, but also to assist in the recovery of degraded environments in the proximity of the mines.